Bioaccessibility of carotenoids from Chlorella vulgaris and Chlamydomonas reinhardtii. (3rd July 2016) - Gille, Andrea; Trautmann, Andreas; Posten, Clemens; Briviba, Karlis
Abstract: Microalgae can contribute to a balanced diet because of their composition. Beside numerous essential nutrients, carotenoids are in the focus for food applications. The bioavailability of carotenoids from photoautotrophic-cultivated Chlorella vulgaris ( C. vulgaris ) and Chlamydomonas reinhardtii ( C. reinhardtii ) was compared. An in vitro digestion model was used to investigate carotenoid bioaccessibility. Furthermore, the effect of sonication on bioaccessibility was assessed. Lutein was the main carotenoid in both species. C. reinhardtii showed higher amounts of lutein and β-carotene than C. vulgaris . In contrast to C. reinhardtii, no β-carotene and only 7% of lutein were bioaccessible in nonsonicated C. vulgaris. Sonication increased the bioaccessibility of carotenoids from C. vulgaris to a level comparable with C. reinhardtii (β-carotene: ≥ 10%; lutein: ≥ 15%). Thus, C. reinhardtii represents a good carotenoid source for potential use in foods without processing, while the application of processing methods, like sonication, is necessary for C. vulgaris .